High-entropy alloy screening method based on lattice distortion and entropy value and hydrogen storage application thereof

By preparing the high-entropy alloy TiFeMnCoVZr, the high entropy value and high lattice distortion degree are used to destroy the oxide layer, and the problem of surfactant site loss caused by the easy oxidation of the TiFe alloy catalyst is solved, and the efficient hydrogen storage performance of MgH2 is achieved.

CN119694445APending Publication Date: 2025-03-25CHONGQING UNIV +1
View PDF 0 Cites 1 Cited by

Patent Information

Application Number
CN202411790890.0
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-06
Publication Date
2025-03-25

AI Technical Summary

Technical Problem

The catalysts in the existing TiFe alloy system have problems with oxidation, resulting in the loss of surfactant sites, which in turn affects the hydrogen storage kinetics of MgH2.

Method used

By preparing the high-entropy alloy TiFeMnCoVZr, the high entropy value and high lattice distortion degree of the high-entropy alloy are used to destroy the density and stability of its surface oxide layer, thereby improving the hydrogen absorption and discharge performance of MgH2.

Benefits of technology

The rapid hydrogen absorption and discharge capacity of MgH2 and the maximum hydrogen absorption and discharge capacity are achieved, reducing the hydrogen release activation energy and improving the dynamic performance of hydrogen storage.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119694445A_ABST
    Figure CN119694445A_ABST
Patent Text Reader

Abstract

The invention discloses a lattice distortion and entropy value-based high-entropy alloy screening method, which comprises the following steps of: firstly, simultaneously calculating the lattice distortion degree and entropy value of a high-entropy alloy, and then determining the components of the high-entropy alloy meeting the requirements according to the screening requirements; according to the Hume-Rother alloy solid solution theory, the lattice distortion degree is calculated; the lattice distortion degree must be greater than or equal to 8.7%, and the upper and lower limit difference must be greater than or equal to 2.0%; entropy calculation is carried out based on the statistical definition of the concept of mixed entropy in statistical mechanics; the entropy value must be greater than or equal to 1.5 R. The obtained TiFeMnCoVZr high-entropy alloy only contains a Laves phase, and when the TiFeMnCoVZr high-entropy alloy is used as a magnesium hydride hydrogen storage material, the maximum hydrogen absorption amount can reach 4.7 wt.%, the maximum hydrogen desorption amount is 4.6 wt.%, and the hydrogen desorption activation energy is 68.9 kJ / mol.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the field of hydrogen storage materials, and in particular relates to a high entropy alloy screening method based on lattice distortion and entropy value and a hydrogen storage application thereof. Background Art

[0002] As a solid hydrogen storage material, magnesium hydride MgH2 has the characteristics of high hydrogen storage capacity, but the high hydrogen release temperature and slow kinetic performance cannot meet the application requirements. Among the common solutions to improve the hydrogen storage performance of MgH2, doping alloy catalysts, such as TiFe alloy system, LaNi5 alloy system and ZrMn2 alloy system, all have the advantages of low cost and significant effect. Among them, in the TiFe alloy system, the Ti element can increase the hydrogen diffusion rate in MgH2, and the Fe element can absorb hydrogen in its lattice, which can not only act as a hydrogen pump, but also provide a diffusion path for hydrogen Fe, that is, both the Ti element and the Fe element themselves have excellent catalytic properties, so that the TiFe alloy system can significantly improve the hydrogen storage performance of MgH2.

[0003] However, such TiFe alloy system catalysts are all prone to oxidation, that is, there is an oxide layer on the surface. This problem directly leads to the technical problem that the TiFe alloy system catalyst has a lack of surface active sites. For example, the existing document 1 ("Hydrogen Kinetics Studies of MgH2-FeTi Composites" 2nd International Conference on Condensed Matter and Applied Physics. 2017) prepared FeTi materials by a smelting method, which can reduce the activation energy of MgH2 to 87.93kJ / mol.

[0004] In order to solve the problem of missing surface active sites caused by the oxide layer, the inventors of the present invention have made previous research results, and the existing document 2 ("Improved hydrogen storage kinetics of MgH2 using TiFe 0.92 Mn 0.04 Co 0.04with in-situ generated α-Fe as catalyst》Materials Reports:Energy.2024,4:100247.) By introducing Mn and Co elements, the activation energy of the kinetic performance of MgH2 is reduced to 84.5 kJ / mol. The principle is that by introducing Co element, the Fe element in TiFe alloy is replaced to form a uniform and stable solid solution structure, thereby improving the hydrogen absorption and desorption performance; by introducing Mn element, α-Fe is promoted to precipitate in situ in TiFe alloy, destroying the original oxide layer and solving the problem of missing surface active sites. At the same time, α-Fe also has the advantage of providing new hydrogen absorption and desorption active sites and channels.

[0005] However, this type of catalyst based on the TiFe alloy system still has the problem of an initial hydrogen desorption temperature higher than 240°C and an activation energy greater than 80 kJ / mol, that is, poor hydrogen desorption kinetics. The reason is that this type of technical solution based on traditional alloy catalysts is composed of 2-4 metal elements. By introducing different metal elements, the corresponding technical effects are achieved through each element component. However, this type of alloy has a low entropy value, with an entropy value of ≤1.5R, that is, a low entropy alloy. The lower entropy value directly leads to the ordering of the atomic arrangement and electronic structure on the alloy surface, which in turn leads to a reduction in the active sites on the surface, which is ultimately reflected in poor catalytic performance.

[0006] In order to solve the above technical problems, the hydrogen storage kinetics of MgH2 can be further improved by adding components and preparing high entropy alloys. The principle is that high entropy alloys HEAs composed of 5 or more metal elements with equiatomic ratios or near equiatomic ratios have good hydrogen storage properties due to the characteristics of the electronic structure and large lattice distortion between different metal elements. It is well known that catalysts with dehydrogenation / hydrogen absorption capabilities can better improve the hydrogen absorption and desorption kinetics of MgH2.

[0007] For example, the existing document 3 ("Surprising cocktail effect in high entropy alloys on catalyzing magnesium hydride for solid-state hydrogen storage" Chem. Eng. J. 2023, 465: 142966.) also obtains the powder of CrMnFeCoNi alloy by the same process as the existing document 2, first using the smelting method and then using the mechanical crushing process; however, the existing document 3 also needs to mechanically ball-mill the powder of the CrMnFeCoNi alloy before compounding with MgH2. Although this technical solution obtains the CrMnFeCoNi high entropy alloy by directly adding components, and the activation energy is reduced to 75.8 kJ / mol, which is lower than the existing document 2, but the steps of the preparation process are increased. The reason is that the preparation process is usually accompanied by grain refinement, and the fine grains will significantly improve the hardness and strength of the material, resulting in the inability to obtain the powder particle size required for ball milling and compounding with MgH2 by mechanical crushing alone. Therefore, a separate ball milling process must be added to further reduce the powder size.

[0008] Obviously, the preparation of high-entropy alloys based on smelting methods cannot overcome the above technical problems in principle. Therefore, high-entropy alloys can be prepared by mechanical alloying. For example, existing document 4 (《Evolution of the Phase and Hydrogen Storage Properties of New-Type VTiCrFeMn High-Entropy Alloy Prepared via Mechanical Alloying》Integr.Ferroelectr, 2023, 235:17-28) successfully synthesized VTiCrFeMn high-entropy alloys by mechanical alloying.

[0009] For example, the existing document 5 (“Hydrogen storage properties of MgTiVZrNb high-entropy alloy and its catalytic effect upon hydrogen storage in Mg” Int. J. Hydrogen Energ. 2024, 50: 749-762) can prepare the high-entropy alloy MgTiVZrNb only by mechanical alloying method.

[0010] Existing documents 4 and 5 achieve mechanical alloying by ball milling, and both directly obtain high entropy alloy powders. Therefore, there is no need for mechanical crushing and mechanical ball milling, which successfully reduces the preparation process. However, taking existing document 5 as an example, the activation energy is higher than that of existing document 2, which is 99.6 kJ / mol. The reason is that in order to achieve a uniform solid solution, form a stable phase and reduce phase separation, thereby improving the stability of the high entropy alloy, elements with similar atomic sizes are used when selecting alloy components. This technical feature leads to a small degree of lattice distortion of the obtained high entropy alloy, which is only 6.4%. That is, it can be seen from the existing literature that only considering the entropy value of the alloy, that is, preparing a high entropy alloy, it is impossible to directly and effectively obtain the technical effect of reducing the activation energy and improving the hydrogen release performance, that is, the entropy value of the multi-component alloy is not the only criterion for determining the catalytic modified MgH2 hydrogen storage kinetics.

[0011] According to existing literature and inventors, the degree of lattice distortion can directly affect hydrogen storage performance. For example, existing document 6 (Structural-regulation of Laves phase high-entropy alloys to catalytically enhance hydrogen desorption from MgH2 J. Alloys Compd., 2024, 997: 174822) prepared single-phase Laves phase ZrNiFeVCr and ZrTiNiFeVMn high entropy alloys with different structures, and reduced the dehydrogenation activation energy of MgH2 to 100.4 kJ / mol and 94.6 kJ / mol, respectively. Comparing the catalytic effects of the two high entropy alloys ZrTiNiFeVMn and ZrNiFeVCr, it can be seen that the reason for the performance difference is that the lattice distortion of the two high entropy alloys is different. The greater the degree of lattice distortion, the lower the activation energy, that is, the degree of lattice distortion is also one of the criteria affecting the catalytic performance. Therefore, when determining the components of high entropy alloys and preparing high entropy alloys, it is also necessary to screen the degree of lattice distortion.

[0012] In order to demonstrate the influence of the above-mentioned lattice distortion degree on the catalytic performance, the existing literature was analyzed.

[0013] The high-entropy alloy prepared in the existing document 7 ("Superior catalytic action of high-entropy alloy on hydrogen sorption properties of MgH2" Int. J. Hydrogen Energ. 2024, 50: 749-762) has a lattice distortion degree of 5.8% and an activation energy of 121 kJ / mol.

[0014] The high entropy alloy prepared in the aforementioned existing document 5 has a lattice distortion degree of 6.4% and an activation energy of 99.6 kJ / mol.

[0015] The high entropy alloy prepared in existing document 8 ("TiVNb-based high entropy alloys as catalysts for enhanced hydrogen storage in nanostructured MgH2" J. Mater. Chem. A. 2023, 11: 4789) has a lattice distortion degree of 8.1% and an activation energy of 96.8 kJ / mol.

[0016] By comparing and analyzing the experimental results of the above existing documents 7, existing document 5 and existing document 8, the following conclusion can be drawn: when the three high entropy alloys with different lattice distortion degrees are respectively ball-milled with MgH2 to prepare hydrogen storage materials, the hydrogen desorption activation energy decreases with the increase of the lattice distortion degree of the high entropy alloy - this conclusion is consistent with the conventional knowledge in this field.

[0017] However, the high entropy alloy prepared in the existing document 9 ("Optimizing FeCoNiCrTi high-entropy alloy with hydrogen pumping effect to boost de / hydrogenation performance of magnesiumhydride". Rare. Met. 2024, 43: 3273-3285) has a lattice distortion of only 6.3%, and its activation energy is only 76.2 kJ / mol, which is lower than that of the existing document, while the activation energy is lower than that of the existing document. Therefore, the experimental data of the existing document show that the relationship between the degree of lattice distortion and the performance of high entropy alloy modified MgH2 is not a simple positive correlation.

[0018] Based on the above analysis, it is found that the entropy value and lattice distortion of the alloy are factors that affect the hydrogen storage performance of MgH2. Therefore, the problem existing in the prior art, that is, the solution is to screen high entropy alloys by considering both the lattice distortion degree and the entropy value at the same time in order to improve the hydrogen storage performance. Summary of the invention

[0019] The object of the present invention is to provide a high entropy alloy screening method based on lattice distortion and entropy value and its hydrogen storage application, which specifically comprises a screening method based on the same inventive concept, a high entropy alloy and a preparation method thereof, and a magnesium hydride hydrogen storage material based on TiFeMnCoVZr high entropy alloy and a preparation method thereof.

[0020] In order to achieve the above-mentioned invention object, the present invention adopts the following inventive concept: in order to obtain a high-entropy alloy with the best catalytic modified MgH2 hydrogen storage performance, the lattice distortion degree and entropy value of the TiFeMnCoVZr high-entropy alloy are calculated at the same time, and then the composition of the TiFeMnCoVZr high-entropy alloy that meets the requirements is determined according to the screening requirements, and the characteristics of the high entropy value and high lattice distortion degree of the high-entropy alloy are utilized to effectively destroy the density and stability of its surface oxide layer, so as to achieve the effect of rapid hydrogen absorption and desorption of MgH2 and the maximum hydrogen absorption and desorption capacity.

[0021] In order to achieve the above-mentioned object of the invention, the present invention adopts the following technical solutions:

[0022] A high entropy alloy screening method based on lattice distortion and entropy value comprises the following steps: first, performing screening calculation of TiFeMnCoVZr high entropy alloy, specifically, calculating the lattice distortion degree and entropy value of the TiFeMnCoVZr high entropy alloy at the same time, and then, according to the screening requirements, determining the composition of the TiFeMnCoVZr high entropy alloy that meets the requirements;

[0023] The method for calculating the degree of lattice distortion is to calculate the degree of lattice distortion of TiFeMnCoVZr high entropy alloy by using Hume-Rothery alloy solid solution theory; the screening requirements for the degree of lattice distortion are that, first, the range of the degree of lattice distortion must be ≥8.7%, and then, within this range, the difference between the upper and lower limits of the degree of lattice distortion must be ≥2.0%;

[0024] The entropy value calculation method is to calculate the entropy value of the TiFeMnCoVZr high entropy alloy based on the statistical definition of the concept of mixed entropy in statistical mechanics; the screening requirement for the entropy value is that the entropy value must be ≥1.5R (R is the ideal gas constant, and its value is 8.314 J / mol·K), that is, it meets the basic requirements of the high entropy alloy.

[0025] A TiFeMnCoVZr high entropy alloy is obtained by ball milling titanium powder, iron powder, manganese powder, cobalt powder, vanadium powder and zirconium powder as raw materials with a material ratio of Ti:Fe:Mn:Co:V:Zr of 1:1:1:1:1:1 to obtain a TiFeMnCoVZr high entropy alloy containing only a Laves phase; the micromorphology is that small alloy particles with a particle size of 1-4 μm are aggregated into aggregates with a particle size of 23-27 μm.

[0026] A preparation method of a TiFeMnCoVZr high entropy alloy comprises the following steps: first, according to a screening result obtained by a screening method for a TiFeMnCoVZr high entropy alloy, titanium powder, iron powder, manganese powder, cobalt powder, vanadium powder and zirconium powder are used as raw materials, and the raw materials are ground and mixed in an argon gas condition at a material amount ratio that meets the screening result to obtain a mixed raw material, and then, under certain conditions, the mixed raw material is ball-milled to obtain a powder of the TiFeMnCoVZr high entropy alloy;

[0027] The molar ratio of Ti:Fe:Mn:Co:V:Zr is 1:1:1:1:1:1;

[0028] The ball milling conditions are as follows: under argon conditions, the grinding balls are stainless steel grinding balls, the ball-to-material ratio is 20:1, the ball milling speed is 270-290rpm, and the ball milling method is forward and reverse intermittent ball milling, wherein the forward ball milling is 10 minutes, paused for 10 minutes, and then reverse ball milling for the same time, and the total ball milling time is 9-11 hours.

[0029] When used as a magnesium hydride hydrogen storage material based on TiFeMnCoVZr high entropy alloy, under the conditions of hydrogen absorption temperature of 250°C and hydrogen absorption pressure of 3MPa, the maximum hydrogen absorption capacity can reach 4.4-4.8wt.%, and 90% of the maximum hydrogen absorption capacity can be reached in 25-30s; under the conditions of hydrogen desorption temperature of 250°C and hydrogen desorption pressure of vacuum, the maximum hydrogen desorption capacity is 4.5-4.7wt.%, and complete hydrogen desorption requires 28-31min, and the hydrogen desorption activation energy is 68.9kJ / mol.

[0030] A method for preparing a magnesium hydride hydrogen storage material based on a TiFeMnCoVZr high entropy alloy comprises the following steps: HEA accounts for a certain mass percentage of the total mass of the hydrogen storage material, HEA and MgH2 are mixed and then subjected to composite ball milling to obtain a magnesium hydride hydrogen storage material based on the TiFeMnCoVZr high entropy alloy;

[0031] The mass percentage of the HEA in the total mass of the hydrogen storage material is 10wt.%;

[0032] The conditions of the composite ball milling are as follows: under argon conditions, the grinding balls are stainless steel grinding balls, the ball-to-material ratio is 40:1, the ball milling speed is 230-250rpm, and the ball milling method is forward and reverse intermittent ball milling, wherein after forward ball milling for 30 minutes, it is paused for 10 minutes, and then reverse ball milling for the same time, and the total ball milling time is 39-41 hours.

[0033] The technical effects of the present invention are as follows after experimental detection:

[0034] The XRD test results show that the TiFeMnCoVZr high entropy alloy only contains Laves phase when the lattice distortion degree is within 8.7%-11.2%; and, MgH2-HEA only contains Laves phase and MgH2 phase.

[0035] The results of SEM and EDS tests show that the average particle size of TiFeMnCoVZr high entropy alloy is an aggregate of 23-27μm, and the components are evenly dispersed without forming element agglomeration or segregation in a certain place; and the average particle size of MgH2-HEA is 2-5μm, showing small particle agglomerations and evenly dispersed distribution of agglomerations.

[0036] The results of hydrogen absorption kinetics test show that under the conditions of hydrogen absorption temperature of 250℃ and hydrogen absorption pressure of 3MPa, the maximum hydrogen absorption amount can reach 4.4-4.8wt.%, and 90% of the maximum hydrogen absorption amount can be reached in 25-30s;

[0037] The results of the hydrogen desorption kinetics test show that under the conditions of a hydrogen desorption temperature of 250°C and a hydrogen desorption pressure of vacuum, the maximum hydrogen desorption amount is 4.5-4.7wt.%, and complete hydrogen desorption requires 28-31 minutes.

[0038] Compared with the prior art, the present invention has the following advantages:

[0039] 1. The high entropy alloy screening method of the present invention successfully screens out high entropy alloys that have both improved kinetic properties and hydrogen storage capacity of MgH2 by combining the effects of lattice distortion and entropy value;

[0040] 2. The screening method of the present invention successfully simplifies the preparation process and reduces production requirements;

[0041] 3. The high entropy alloy obtained by the present invention has a large degree of lattice distortion, that is, there are a large number of dislocations and defects, which successfully destroys the compactness and stability of the alloy oxide layer, thereby increasing the active sites in the hydrogen storage reaction process.

[0042] 3. The present invention combines the catalytic effect of high entropy alloys with their lattice distortion and entropy value, and successfully screens out high entropy alloys that can simultaneously improve the kinetic properties and hydrogen storage capacity of MgH2. BRIEF DESCRIPTION OF THE DRAWINGS

[0043] Figure 1 is the XRD pattern of the TiFeMnCoVZr high entropy alloy in Example 1;

[0044] Figure 2 The SEM image and EDS scan of MgH2-HEA-1 in Example 1;

[0045] Figure 3The XRD patterns of MgH2-HEA-1 in Example 1 after ball milling, hydrogen release, and hydrogen absorption;

[0046] Figure 4 The SEM images of MgH2-HEA-1 prepared in Example 1 at different ball milling times at a scale of 20 μm and the corresponding EDS surface scanning images of the ball milling state;

[0047] Figure 5 The isothermal hydrogen absorption curves of Example 1, Example 2, Example 3, Example 4 and Comparative Example 1 of the present invention at 250° C. under a hydrogen pressure of 3 MPa;

[0048] Figure 6 The isothermal hydrogen desorption curves of Example 1, Example 2, Example 3, Example 4 and Comparative Example 1 in the present invention at 250° C. under vacuum are shown. DETAILED DESCRIPTION

[0049] The present invention is further described in detail through embodiments and in conjunction with the accompanying drawings, but the present invention is not limited thereto.

[0050] Example 1

[0051] A screening method for a TiFeMnCoVZr high entropy alloy comprises the following steps: first, performing screening calculations on the TiFeMnCoVZr high entropy alloy, specifically, simultaneously calculating the lattice distortion degree and entropy value of the TiFeMnCoVZr high entropy alloy, and then, according to screening requirements, determining the composition of the TiFeMnCoVZr high entropy alloy that meets the requirements.

[0052] The method for calculating the degree of lattice distortion is to calculate the degree of lattice distortion of TiFeMnCoVZr high entropy alloy by using Hume-Rothery alloy solid solution theory. The calculation results are shown in Table 1.

[0053] Table 1 Calculation results of lattice distortion of TiFeMnCoVZr high entropy alloy

[0054]

[0055]

[0056] The entropy value calculation method is to calculate the entropy value of the TiFeMnCoVZr high entropy alloy based on the statistical definition of the concept of mixed entropy in statistical mechanics, and the calculation results are shown in Table 2.

[0057] Table 2 Calculation results of entropy value of TiFeMnCoVZr high entropy alloy

[0058]

[0059]

[0060] In the screening requirements,

[0061] The screening requirements for the degree of lattice distortion are: first, the range of the degree of lattice distortion must be ≥ 8.7%, and then, within this range, the difference between the upper and lower limits of the degree of lattice distortion must be ≥ 2.0%;

[0062] The screening requirement for entropy value is that the entropy value must be ≥1.5R, which means that it meets the basic requirements of high entropy alloys;

[0063] The screening process of the specific embodiment 1, that is, the TiFeMnCoVZr high entropy alloy that meets the requirements is, according to the screening requirements of the lattice distortion degree, the TiFeMnCoVZr with a difference between the upper and lower limits of the lattice distortion degree of 2.5% is selected. x Alloy series; according to the screening requirements of entropy value, TiFeMnCoVZr1 with the maximum entropy value of 1.79R is selected, that is, the material ratio of Ti:Fe:Mn:Co:V:Zr is 1:1:1:1:1:1 in accordance with the screening requirements;

[0064] A preparation method of a TiFeMnCoVZr high entropy alloy comprises the following steps: first, according to a screening result obtained by a screening method for a TiFeMnCoVZr high entropy alloy, titanium powder, iron powder, manganese powder, cobalt powder, vanadium powder and zirconium powder are used as raw materials, and the raw materials are ground and mixed in an argon gas condition at a material amount ratio that meets the screening result to obtain a mixed raw material, and then, under certain conditions, the mixed raw material is ball-milled to obtain a powder of a TiFeMnCoVZr high entropy alloy, referred to as HEA-1;

[0065] The substance amount ratio of the screening result is that the substance amount ratio of Ti:Fe:Mn:Co:V:Zr is 1:1:1:1:1:1;

[0066] In the preparation method of the TiFeMnCoVZr high entropy alloy, the ball milling conditions are as follows: under argon conditions, the grinding balls are stainless steel grinding balls, the ball-to-material ratio is 20:1, the ball milling speed is 280 rpm, and the ball milling method is forward and reverse intermittent ball milling, wherein the forward ball milling is 10 minutes, paused for 10 minutes, and then reverse ball milling for the same time, and the total ball milling time is 10 hours.

[0067] In order to prove the phase types of HEA-1 and the phase changes during the preparation process, XRD tests were performed; at the same time, in order to prove the influence of the ball milling process on the phase composition of the alloy, XRD tests were performed on the ground mixed raw materials for comparison. Figure 1 As shown,

[0068] The XRD test results of the mixed raw materials are as follows: Figure 1 As shown, the mixed raw material contains characteristic peaks of Ti metal, Fe metal, Mn metal, Co metal, V metal and Zr metal at the same time. The test results show that after grinding and mixing, the mixed raw material still remains in the state of various raw metal elements, that is, the grinding and mixing process is physical mixing;

[0069] The XRD test results of HEA-1 are as follows Figure 1 As shown, HEA-1 only has diffraction peaks at 30-50°, that is, HEA-1 only contains Laves phase, and does not contain diffraction peaks of various raw metal elements. The test results show that after ball milling, that is, mechanical alloying process, the mixed raw materials are transformed from metal elements to Laves single phase, that is, chemical reaction occurs during mechanical alloying process.

[0070] In order to further prove the element distribution of HEA-1, that is, its uniform distribution of components consistent with high entropy alloy, EDS test was carried out. Figure 2 As shown in the figure, each component element in HEA-1 is evenly dispersed, that is, there is no element agglomeration or segregation. The test results show that HEA-1 meets the characteristics of high entropy alloys.

[0071] Through XRD test, EDS test and entropy value calculation results, it can be proved that HEA-1 obtained in step 2 is a Laves single-phase high entropy alloy.

[0072] In order to verify the microstructure of HEA-1, SEM test was performed, and the test results are shown in Figure 3 As shown, HEA-1 is formed by small alloy particles with a particle size of 1-4 μm agglomerating into aggregates with a particle size of 23-27 μm. The test results show that in the preparation process under the mechanical alloying conditions of the present invention, no cold welding phenomenon occurs, that is, high entropy alloy powder is successfully obtained.

[0073] A method for preparing a magnesium hydride hydrogen storage material based on a TiFeMnCoVZr high entropy alloy comprises the following steps: HEA-1 accounts for 10wt.% of the total mass of the hydrogen storage material, HEA-1 and MgH2 are mixed and subjected to composite ball milling to obtain a magnesium hydride hydrogen storage material based on a TiFeMnCoVZr high entropy alloy, referred to as MgH2-HEA-1;

[0074] In the preparation method of the magnesium hydride hydrogen storage material based on TiFeMnCoVZr high entropy alloy, the conditions of composite ball milling are as follows: under argon conditions, the grinding balls are stainless steel grinding balls, the ball-to-material ratio is 40:1, the ball milling speed is 240 rpm, and the ball milling method is forward and reverse intermittent ball milling, wherein after forward ball milling for 30 minutes, it is paused for 10 minutes, and then reverse ball milling for the same time, and the total ball milling time is 40 hours.

[0075] In order to prove the phase type of MgH2-HEA-1 and the phase change during the preparation process, XRD test was carried out. The test results are shown in Figure 3 As shown, MgH2-HEA-1 contains characteristic peaks of both Laves phase and MgH2 phase. The test results show that during the composite ball milling process, MgH2 and HEA-1 did not react chemically, that is, the composite ball milling process was only physical mixing.

[0076] In order to further prove the element distribution of MgH2-HEA-1, EDS test was carried out. The test results are as follows Figure 4 As shown, each component element in MgH2-HEA-1, including Mg element, is evenly dispersed. The test results show that the composite degree of HEA-1 and MgH2 in MgH2-HEA-1 is good, and HEA-1 still maintains the state of high entropy alloy.

[0077] Combining the XRD test and EDS test results, it can be seen that after composite ball milling, HEA-1 still maintains the state of high entropy alloy in MgH2-HEA-1.

[0078] In order to verify the microstructure of MgH2-HEA-1, SEM test was performed. The test results are shown in Figure 4 As shown, MgH2-HEA-1 is presented as small particles uniformly dispersed, and the particle size is 2-5 μm. The test results show that after the composite ball milling in step 3, a hydrogen storage material with uniform particle size reaching the micron level is obtained.

[0079] In order to prove the hydrogen storage performance of the obtained MgH2-HEA-1, hydrogen absorption and desorption kinetics tests were carried out.

[0080] The results of hydrogen absorption kinetics test are as follows Figure 5 As shown in Table 3, under the conditions of hydrogen absorption temperature of 250°C and hydrogen absorption pressure of 3MPa, the maximum hydrogen absorption amount can reach 4.7wt.%, and 90% of the maximum hydrogen absorption amount can be achieved in 27s;

[0081] The results of hydrogen release kinetics test are as follows Figure 6 As shown in Table 3, under the conditions of hydrogen desorption temperature of 250°C and vacuum pressure, the maximum hydrogen desorption amount is 4.6wt.%, and complete hydrogen desorption requires 28min;

[0082] The test results show that MgH2-HEA-1 has good kinetic properties, especially at a lower hydrogen absorption / desorption temperature, i.e. 250°C, and has both high hydrogen desorption capacity and high hydrogen desorption rate.

[0083] Table 3 Hydrogen absorption and desorption performance of magnesium hydride hydrogen storage materials based on TiFeMnCoVZr high entropy alloy at 250℃

[0084]

[0085] In order to further prove the dehydrogenation kinetics of MgH2-HEA-1 obtained in step 3, quantitative analysis was performed and the dehydrogenation activation energy was calculated by Chou model. The dehydrogenation activation energy of MgH2-HEA-1 is 68.9 kJ / mol.

[0086] In order to demonstrate the technical effects of the preparation method of the present invention and the obtained MgH2-HEA-1, a comparative analysis was conducted by citing existing literature, and the specific values ​​are shown in Table 2.

[0087] Table 4 Summary of preparation methods and hydrogen storage performance of other system materials

[0088]

[0089] 1-1. ZFLi, YFLu, JFWang, et al. Improved hydrogen storage kinetics of MgH2 using TiFe 0.92 Mn 0.04 Co 0.04 with in-situ generatedα-Fe ascatalyst.Materials Reports:Energy.2024,4:100247.

[0090] 1-2. L.Wang, LTZhang,

[0091] 1-3. T.Zhong, HYZhang, MC Song, et al. FeCoNiCrMo high entropy alloynanosheets catalyzed magnesium hydride for solid-state hydrogen storage. Int.J.Min.Met.Mater.2023,30:2270.

[0092] The existing document 1-1 is the previous work result of the inventor of the present invention. The technical solution adopted is to obtain TiFeMnCo alloy by first adopting a smelting method and then mechanically crushing, and then compounding with MgH2 to achieve a technical effect of an activation energy of 84.5 kJ / mol. However, since the TiFeMnCo alloy is a quaternary alloy, its entropy value is less than 1R, that is, it is a low-entropy alloy, so the effect of reducing the activation energy cannot reach the level of a high-entropy alloy.

[0093] In order to solve the above technical problems, a high entropy alloy can be prepared by increasing the number of components to improve the effect of reducing the activation energy, that is, the technical solution adopted by the existing documents 1-2, specifically, the powder of the CrMnFeCoNi alloy is obtained by first adopting the smelting method and then adopting the mechanical crushing process as the existing document 1; however, the existing documents 1-2 also need to mechanically ball mill the powder of the CrMnFeCoNi alloy before compounding with MgH2. Although the technical solution obtains the CrMnFeCoNi high entropy alloy by directly increasing the components, and the activation energy is reduced to 75.8kJ / mol, which is lower than the existing document 1-1, the steps of the preparation process are increased. The technical solution directly leads to the technical problem of increasing the preparation process, and the reason is that the high entropy alloy is usually accompanied by grain refinement in its preparation process, and the fine grains will significantly improve the hardness and strength of the material, resulting in the inability to obtain the powder particle size required for ball milling with MgH2 by mechanical crushing alone, so it is necessary to increase the separate ball milling process to further reduce the powder size.

[0094] Obviously, the preparation of high entropy alloys based on the smelting method cannot overcome the above technical problems in principle. Therefore, high entropy alloys can be prepared by mechanical alloying. For example, the existing documents 1-3 adopt a technical solution that only mechanical alloying method can be used to prepare the high entropy alloy MgTiVZrNb. This technical solution realizes mechanical alloying by ball milling to directly obtain high entropy alloy powder. Therefore, there is no need for mechanical crushing and mechanical ball milling, which successfully reduces the preparation process. However, the activation energy obtained by this technical solution is higher than that of the existing document 1-1, which is 99.6kJ / mol. The reason is that according to the research of the inventor, in order to achieve a uniform solid solution, form a stable phase and reduce phase separation, thereby improving the stability of the high entropy alloy, so when selecting the alloy composition, elements with similar atomic sizes are used. This technical feature leads to a small degree of lattice distortion of the obtained high entropy alloy, which is only 6.4% - according to the research of the inventor, the degree of lattice distortion can directly affect the hydrogen storage performance.

[0095] Through the analysis of the above existing literature, it can be seen that only considering the entropy value of the alloy, that is, preparing high entropy alloys, cannot directly and effectively obtain the technical effect of reducing activation energy and improving hydrogen desorption performance. That is, the entropy value of the multi-component alloy is not the only criterion for determining the catalytic modified MgH2 hydrogen storage kinetics.

[0096] According to the inventors' research, the degree of lattice distortion of the alloy is also one of the criteria that affects the catalytic performance. Therefore, when determining the components of high entropy alloys and preparing high entropy alloys, the degree of lattice distortion also needs to be screened. The inventors compared and analyzed the relationship between the degree of lattice distortion of high entropy alloys and hydrogen storage performance in existing literature, and the specific values ​​are shown in Table 5.

[0097] Table 5 Summary of lattice distortion and hydrogen storage performance of high entropy alloys of other system materials

[0098]

[0099] 2-1. JXZhang, H.Liu, CSZhou, et al.TiVNb-based high entropy alloys ascatalysts for enhanced hydrogen storage in nanostructuredMgH2.J.Mater.Chem.A.2023,11:4789.

[0100] 2-2. SPWu, YPChen, W.Kang, et al. Hydrogen storage properties ofMgTiVZrNb high-entropy alloy and its catalytic effect upon hydrogen storage in Mg.Int.J.Hydrogen Energ.2024,50:1113-1128.

[0101] 2-3. SK Verma, SS Mishra, NK Mukhopadhyay, et al. Superior catalytic action of high-entropy alloy on hydrogen sorption properties of MgH2. Int. J. Hydrogen Energ. 2024, 50: 749-762.

[0102] 2-4. MCSong, FYWu, YQJiang, et al. Optimizing FeCoNiCrTi high-entropy alloy with hydrogen pumping effect to boost de / hydrogenation performance of magnesium hydride. Rare. Met. 2024, 43: 3273-3285.

[0103] By comparing and analyzing the experimental results of existing documents 2-1, 2-2 and 2-3, the following conclusion can be drawn: when three high entropy alloys with different lattice distortion degrees are respectively ball-milled with MgH2 to prepare hydrogen storage materials, the activation energy of hydrogen release decreases as the lattice distortion degree of the high entropy alloy increases. This conclusion is consistent with conventional knowledge in the field.

[0104] However, the lattice distortion degree of the high entropy alloy in the existing document 2-4 is only 6.3%, which is lower than that of the existing documents 2-1 and 2-3, but has the lowest dehydrogenation activation energy. Therefore, the relationship between the lattice distortion degree and the performance of the high entropy alloy modified MgH2 is not a simple positive correlation.

[0105] Based on the above analysis, the inventors of the present invention have found that the entropy value and the degree of lattice distortion of the alloy are both influencing factors affecting the hydrogen storage performance of MgH2. Therefore, based on this finding, the present invention proposes a screening method for high entropy alloys that simultaneously considers the degree of lattice distortion and the entropy value.

[0106] In order to prove the phase types of HEA-1 before and after hydrogen absorption and desorption, that is, the phase changes during the reaction process, XRD test was carried out. The test results are as follows Figure 3 As shown,

[0107] The XRD test results of MgH2-HEA-1 after dehydrogenation are as follows: Figure 3 As shown, only Mg phase and Laves phase exist, and MgH2 phase does not exist. The test results show that during the dehydrogenation process, only the reaction of MgH2 phase completely transforming into Mg phase occurs, that is, during the dehydrogenation reaction, the high entropy alloy still maintains its Laves phase state;

[0108] The XRD test results of MgH2-HEA-1 after hydrogen absorption are as follows: Figure 3 As shown, only MgH2 phase and Laves phase exist, and Mg phase does not exist. The test results show that during the hydrogen absorption process, only the reaction of Mg phase completely transforming into MgH2 phase occurs, that is, during the hydrogen release reaction, the high entropy alloy still maintains its Laves phase state.

[0109] Combining the above test results of hydrogen release and re-absorption, it can be seen that the hydrogen absorption / desorption process is a reversible process, that is, only the mutual transformation of the Mg phase and the MgH2 phase occurs; and the high entropy alloy remains in the Laves phase state, that is, the catalyst in the reaction process, and does not directly participate in the hydrogen absorption / desorption reaction. The basic principle of high entropy alloy as a catalyst to improve the hydrogen absorption and desorption performance is that the lattice distortion on the surface of the high entropy alloy provides more active sites, providing more effective channels for hydrogen diffusion, thereby improving the kinetic performance of MgH2.

[0110] In order to demonstrate the influence of the degree of lattice distortion on the hydrogen storage performance of MgH2, Examples 2, 3 and 4 are provided. By adjusting the content of the Zr element, TiFeMnCoVZr with lattice distortion degrees of 8.7%, 10.9% and 11.2% are obtained respectively.

[0111] Example 2

[0112] A method for preparing a magnesium hydride hydrogen storage material based on a TiFeMnCoVZr high entropy alloy with a lattice distortion degree of 8.7%, wherein the steps not particularly described are the same as those in Example 1, except that: a TiFeMnCoVZr high entropy alloy having a lattice distortion degree of 8.7% and an entropy value of 1.75R is screened out according to a screening method for TiFeMnCoVZr high entropy alloys, that is, a TiFeMnCoVZr high entropy alloy having a composition of Ti:Fe:Mn:Co:V:Zr having a substance molar ratio of 1:1:1:1:1:0.5 that meets the screening requirements, the obtained high entropy alloy is referred to as HEA-0.5, and the obtained magnesium hydride hydrogen storage material based on the TiFeMnCoVZr high entropy alloy is referred to as MgH2-HEA-0.5.

[0113] The XRD test results of HEA-0.5 are as follows Figure 1 As shown, HEA-0.5 has the diffraction peak of Laves phase only at 30-50°, which is the same as that of HEA-1.

[0114] The results of the hydrogen absorption kinetics test of MgH2-HEA-0.5 are as follows: Figure 5 As shown in Table 3, under the conditions of hydrogen absorption temperature of 250°C and hydrogen absorption pressure of 3MPa, the maximum hydrogen absorption amount is 4.4wt.%, and it takes 18s to reach 90% of the maximum hydrogen absorption amount;

[0115] The results of the hydrogen release kinetics test of MgH2-HEA-0.5 are as follows: Figure 6 As shown in Table 3, under the conditions of a dehydrogenation temperature of 250° C. and a vacuum dehydrogenation pressure, the maximum dehydrogenation amount is 4.7 wt.%, 32 min is required for complete dehydrogenation, and the dehydrogenation activation energy is 74.8 kJ / mol.

[0116] Example 3

[0117] A method for preparing a magnesium hydride hydrogen storage material based on a TiFeMnCoVZr high entropy alloy with a lattice distortion degree of 10.9%. The steps not particularly described are the same as those in Example 1, except that: a TiFeMnCoVZr high entropy alloy having a lattice distortion degree of 10.9% and an entropy value of 1.74R is screened out according to a screening method for TiFeMnCoVZr high entropy alloys, that is, a TiFeMnCoVZr high entropy alloy having a composition of Ti:Fe:Mn:Co:V:Zr with a molar ratio of 1:1:1:1:1:2 is met in accordance with the screening requirements. The obtained high entropy alloy is referred to as HEA-2, and the obtained magnesium hydride hydrogen storage material based on the TiFeMnCoVZr high entropy alloy is referred to as MgH2-HEA-2.

[0118] The XRD test results of HEA-2 are as follows Figure 1 As shown, HEA-2 has only the diffraction peak of the Laves phase at 30-50°, which is the same as that of HEA-1.

[0119] The results of the hydrogen absorption kinetics test of MgH2-HEA-2 are as follows: Figure 5 As shown in Table 3, under the conditions of hydrogen absorption temperature of 250°C and hydrogen absorption pressure of 3MPa, the maximum hydrogen absorption amount is 4.5wt.%, and it takes 46s to reach 90% of the maximum hydrogen absorption amount;

[0120] The results of the hydrogen release kinetics test of MgH2-HEA-2 are as follows: Figure 6 As shown in Table 3, under the conditions of a dehydrogenation temperature of 250° C. and a vacuum dehydrogenation pressure, the maximum dehydrogenation amount is 4.3 wt.%, 23 min is required for complete dehydrogenation, and the dehydrogenation activation energy is 65.6 kJ / mol.

[0121] Example 4

[0122] A method for preparing a magnesium hydride hydrogen storage material based on a TiFeMnCoVZr high entropy alloy with a lattice distortion degree of 11.2%. The steps not particularly described are the same as those in Example 1, except that: a TiFeMnCoVZr high entropy alloy having a lattice distortion degree of 11.2% and an entropy value of 1.67R is screened out according to a screening method for TiFeMnCoVZr high entropy alloys, that is, a TiFeMnCoVZr high entropy alloy having a composition of Ti:Fe:Mn:Co:V:Zr with a molar ratio of 1:1:1:1:1:3 is met in accordance with the screening requirements. The obtained high entropy alloy is referred to as HEA-3, and the obtained magnesium hydride hydrogen storage material based on the TiFeMnCoVZr high entropy alloy is referred to as MgH2-HEA-3.

[0123] The XRD test results of HEA-3 are as follows Figure 1 As shown, HEA-3 has only the diffraction peak of the Laves phase at 30-50°, which is the same as that of HEA-1.

[0124] The results of the hydrogen absorption kinetics test of MgH2-HEA-3 are as follows: Figure 5 As shown in Table 3, under the conditions of hydrogen absorption temperature of 250°C and hydrogen absorption pressure of 3MPa, the maximum hydrogen absorption amount is 4.1wt.%, and it takes 30s to reach 90% of the maximum hydrogen absorption amount;

[0125] The results of hydrogen release kinetics test of MgH2-HEA-3 are as follows: Figure 6 As shown in Table 3, under the conditions of a dehydrogenation temperature of 250° C. and a vacuum dehydrogenation pressure, the maximum dehydrogenation amount is 4.1 wt.%, 16 min is required for complete dehydrogenation, and the dehydrogenation activation energy is 63.4 kJ / mol.

[0126] By comparing Example 1, Example 2, Example 3 and Example 4, the following conclusions can be drawn:

[0127] 1. With the increase of lattice distortion, the effect of high entropy alloy on the kinetic properties of MgH2 is enhanced, mainly because:

[0128] 1.1. The greater the degree of lattice distortion of HEAs, the more crystal defects there are, thus forming more diffusion channels, changing the diffusion path of hydrogen atoms in the material and increasing the hydrogen release rate;

[0129] 1.2. The higher the degree of lattice distortion, the higher the lattice distortion energy of the interface, which increases the kinetic energy of the MgH2 dehydrogenation process and reduces the kinetic energy barrier of hydrogenation / dehydrogenation.

[0130] Among the various components of high entropy alloys, the Zr element has the function of greatly adjusting the degree of lattice distortion of high entropy alloys.

[0131] 2. The hydrogen storage capacity of MgH2 increases first and then decreases, which is consistent with the law that the entropy value increases first and then decreases. This is mainly because:

[0132] 2.1. The higher the entropy value of HEAs, the greater the phase stability of high entropy alloys at high temperatures, which helps the Laves phase maintain a stable phase during the reaction process, reduces phase separation and grain growth, and thus improves the reversible absorption and release capacity of hydrogen;

[0133] 2.2. The high entropy effect of high entropy alloys can improve the diffusivity of hydrogen. Therefore, the higher the entropy value of the high entropy alloy, the greater the maximum hydrogen release amount.

[0134] In order to demonstrate the catalytic effect of TiFeMnCoVZr high entropy alloy, Comparative Example 1 is provided, in which pure ball-milled MgH2 without adding TiFeMnCoVZr is used as a basic comparative example.

[0135] Comparative Example 1

[0136] A magnesium hydride hydrogen storage material without alloy powder added, the steps not specifically described are the same as those in Example 1, except that: there is no need to screen and prepare high entropy alloys, and in the preparation method of the hydrogen storage material, the high entropy alloy powder accounts for 0wt.% of the total mass of the composite hydrogen storage material, that is, no high entropy alloy powder is added, and the obtained material is named MgH2.

[0137] In order to demonstrate the hydrogen storage performance of MgH2, hydrogen absorption and desorption kinetic tests were carried out.

[0138] The results of hydrogen absorption kinetics test are as follows Figure 5 As shown, at 250 °C and 3 MPa, the maximum hydrogen absorption is 5.9 wt.%, and the time required to reach 90% of the maximum hydrogen absorption is 20 s;

[0139] The results of hydrogen release kinetics test are as follows Figure 6 As shown, under vacuum conditions at 250°C, the amount of hydrogen released in 30 min is only 2.4 wt.%.

[0140] Comparing the hydrogen absorption and desorption test results with those of various embodiments, it can be found that the hydrogen absorption kinetics of all embodiments of the present invention are significantly improved compared with the comparative examples: the hydrogen desorption rate is increased by 40-76%; the hydrogen desorption temperature is reduced to 219-240°C; and the hydrogen desorption activation energy is reduced by 50-58%.

[0141] The reason is that TiFeMnCoVZr, as a high entropy alloy, has a significant lattice distortion effect, so the following technical effects are obtained:

[0142] 1. The increase in lattice distortion directly increases the specific surface area of ​​high entropy alloys and increases the diffusion channels of hydrogen, thereby improving the kinetic properties of MgH2;

[0143] 2. HEA forms a local high-concentration hydrogen region on the surface of MgH2, promoting the nucleation and growth of hydride, that is, providing nucleation sites, thereby improving the kinetic properties of MgH2.

Claims

1. A high entropy alloy screening method based on lattice distortion and entropy value, characterized in that The following steps are involved: Firstly, a screening calculation of TiFeMnCoVZr high entropy alloy is performed, specifically, the lattice distortion degree and entropy value of TiFeMnCoVZr high entropy alloy are calculated at the same time, and then, according to the screening requirements, the composition of TiFeMnCoVZr high entropy alloy that meets the requirements is determined; The method for calculating the degree of lattice distortion is to calculate the degree of lattice distortion of TiFeMnCoVZr high entropy alloy by using Hume-Rothery alloy solid solution theory; The method for calculating the entropy value is to calculate the entropy value of the TiFeMnCoVZr high entropy alloy based on the statistical definition of the concept of mixed entropy in statistical mechanics.

2. The high entropy alloy screening method according to claim 1, characterized in that: In the screening requirements, The screening requirements for the degree of lattice distortion are: first, the range of the degree of lattice distortion must be ≥ 8.7%, and then, within this range, the difference between the upper and lower limits of the degree of lattice distortion must be ≥ 2.0%; The screening requirement for entropy value is that the entropy value must be ≥1.5R, which means it meets the basic requirements of high entropy alloys.

3. A TiFeMnCoVZr high entropy alloy, characterized in that: Using titanium powder, iron powder, manganese powder, cobalt powder, vanadium powder and zirconium powder as raw materials, ball milling with the molar ratio of Ti:Fe:Mn:Co:V:Zr being 1:1:1:1:1:1 can obtain a TiFeMnCoVZr high entropy alloy containing only Laves phase.

4. The TiFeMnCoVZr high entropy alloy according to claim 3, characterized in that: The microstructure is that small alloy particles with a particle size of 1-4 μm are aggregated into aggregates with a particle size of 23-27 μm.

5. A method for preparing a TiFeMnCoVZr high entropy alloy, characterized in that The following steps are involved: Firstly, according to the screening results obtained by the screening method of TiFeMnCoVZr high entropy alloy, titanium powder, iron powder, manganese powder, cobalt powder, vanadium powder and zirconium powder are used as raw materials, and the raw materials are ground and mixed under argon conditions in a substance amount ratio that meets the screening results to obtain a mixed raw material. Then, under certain conditions, the mixed raw material is ball milled to obtain TiFeMnCoVZr high entropy alloy powder.

6. The preparation method according to claim 5, characterized in that the molar ratio of Ti:Fe:Mn:Co:V:Zr is 1:1:1:1:1:1; The ball milling conditions are as follows: under argon conditions, the grinding balls are stainless steel grinding balls, the ball-to-material ratio is 20:1, the ball milling speed is 270-290 rpm, and the ball milling method is forward and reverse intermittent ball milling, wherein: Mill in the forward direction for 10 minutes, pause for 10 minutes, and then mill in the reverse direction for the same time. The total milling time is 9-11 hours.

7. A TiFeMnCoVZr high entropy alloy, characterized in that: When used as a magnesium hydride hydrogen storage material based on TiFeMnCoVZr high entropy alloy, the maximum hydrogen absorption capacity can reach 4.4-4.8wt.% under the conditions of hydrogen absorption temperature of 250°C and hydrogen absorption pressure of 3MPa; under the conditions of hydrogen desorption temperature of 250°C and hydrogen desorption pressure of vacuum, the maximum hydrogen desorption capacity is 4.5-4.7wt.%, and complete hydrogen desorption requires 28-31 minutes, and the hydrogen desorption activation energy is 68.9kJ / mol.

8. A method for preparing a magnesium hydride hydrogen storage material based on TiFeMnCoVZr high entropy alloy, characterized in that The following steps are involved: With HEA accounting for a certain mass percentage of the total mass of the hydrogen storage material, HEA and MgH2 are mixed and then subjected to composite ball milling to obtain magnesium hydride hydrogen storage material based on TiFeMnCoVZr high entropy alloy.

9. The preparation method according to claim 8, characterized in that: The mass percentage of the HEA in the total mass of the hydrogen storage material is 10wt.%; The conditions of the composite ball milling are as follows: under argon conditions, the grinding balls are stainless steel grinding balls, the ball-to-material ratio is 40:1, the ball milling speed is 230-250rpm, and the ball milling method is forward and reverse intermittent ball milling, wherein after forward ball milling for 30 minutes, it is paused for 10 minutes, and then reverse ball milling for the same time, and the total ball milling time is 39-41 hours.

Citation Information

Cited By

  • Intelligent design method of single-phase face-centered cubic high-entropy alloy with large lattice distortion

    CN121393673A